Еврейское измерение Киева в „Кровавой шутке” Шолом-Алейхема - Bortnowski, Antoni (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
Sholem Aleichem is one of the authors of modern Jewish literature in Yiddish, and most of his works are closely related to the realities of Eastern Europe. In his books the writer presents, among others, images of life of the Jewish community in pre- revolutionary Kiev. His novel, The Bloody Hoax, is particularly noteworthy in this case and it has become the main object of research in this paper. The story of the novel mostly takes place in an unnamed city, the prototype of which has become a historical Kiev. The Bloody Hoax, the plot of which is largely based on real events, shows the specificity of life of the Jewish community in the big city, and the problems its representative shave to face.